2022
DOI: 10.1021/acs.orglett.2c01295
|View full text |Cite
|
Sign up to set email alerts
|

Development of Fmoc-Protected Bis-Amino Acids toward Automated Synthesis of Highly Functionalized Spiroligomers

Abstract: We report the fluorenylmethoxycarbonyl (Fmoc) protection of functionalized bis-amino acid building blocks using a temporary Cu2+ complexation strategy, together with an efficient multikilogram-scale synthesis of bis-amino acid precursors. This allows the synthesis of stereochemically and functionally diverse spiroligomers utilizing solid-phase Fmoc/tBu chemistry to facilitate the development of applications. Four tetramers were assembled on a semiautomated microwave peptide synthesizer. We determined their sec… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
5
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
5

Relationship

2
3

Authors

Journals

citations
Cited by 5 publications
(5 citation statements)
references
References 26 publications
(41 reference statements)
0
5
0
Order By: Relevance
“…In 1980 Magnus, Clardy et al reported oligospirotetrahydrofurans that possess an overall structure described by the authors as a "primary helix" 46 . Schafmeister's "spiroligomers" comprise a repeating spiro-linked diketopiperazine-pyrrolidine motif and have been highly successful in inhibiting protein-protein interactions and as enzyme mimetics [47][48][49][50][51][52][53][54][55][56][57] , though the limited flexibility in these systems has led to the authors considering them a separate class from foldamers 52 . In 2008 Rajamohanan, Hofmann and Sanjayan developed spirobi(indane) oligoamide foldamers which fold in a controlled manner due to the formation of a bifurcated hydrogen bond, though the monomers were racemic so likely a mixture of stereoisomers were formed 58,59 .…”
mentioning
confidence: 99%
“…In 1980 Magnus, Clardy et al reported oligospirotetrahydrofurans that possess an overall structure described by the authors as a "primary helix" 46 . Schafmeister's "spiroligomers" comprise a repeating spiro-linked diketopiperazine-pyrrolidine motif and have been highly successful in inhibiting protein-protein interactions and as enzyme mimetics [47][48][49][50][51][52][53][54][55][56][57] , though the limited flexibility in these systems has led to the authors considering them a separate class from foldamers 52 . In 2008 Rajamohanan, Hofmann and Sanjayan developed spirobi(indane) oligoamide foldamers which fold in a controlled manner due to the formation of a bifurcated hydrogen bond, though the monomers were racemic so likely a mixture of stereoisomers were formed 58,59 .…”
mentioning
confidence: 99%
“…[43] Beyond that, the shape persistency of this new class of covalently constrained macrocycles supported by ROESY and the membrane selectivity will enable us to leverage their enormous diversity in 3D structure and chemical functionality to develop new capabilities in separations and encapsulation. [28]…”
Section: Methodsmentioning
confidence: 99%
“…Spiroligomer‐based macrocycles have higher structural diversity than cyclodextrins and other symmetric mimics like calixarenes or trianglamines used to form membranes, [41, 42] providing better tunability to separation properties. Our recent innovations in large‐scale building block synthesis (<$10/g) [28] and automated high‐throughput spiroligomer assembly (unpublished work), along with new techniques to reduce material consumption, such as 3D printed membranes, have dramatically lowered the cost of macrocycles to support practical applications [43] . Beyond that, the shape persistency of this new class of covalently constrained macrocycles supported by ROESY and the membrane selectivity will enable us to leverage their enormous diversity in 3D structure and chemical functionality to develop new capabilities in separations and encapsulation [28] …”
Section: Figurementioning
confidence: 99%
See 2 more Smart Citations